Intellectual property rights, foreign direct investment and competition issues in developing countries. (1st January 2000) - Maskus, Keith E.; Yang, Guifang
The relationships between intellectual property rights and foreign direct investment are subtle and complex, though potentially important as developing countries strengthen their systems for protecting such rights. There is emerging empirical evidence that both investment and licensing of sophisticated technologies depend positively on the strength of intellectual property rights. This may raise concerns about anti-competitive abuse of such rights in developing economies, pointing to the need for complementary regulation to promote dynamic competition.